Mevalonate kinase deficiency: enlarging the clinical and biochemical spectrum - Prietsch, Viola; Mayatepek, Ertan; Krastel, Hermann; Haas, Dorothea; Zundel, Dorothee; Waterham, Hans R.; Wanders, Ronald J. A.; Gibson, K. Michael; Hoffmann, Georg F. (Pediatrics, 2003)
Objective. Mevalonic aciduria as a result of mevalonate kinase deficiency is an inborn error of cholesterol biosynthesis characterized by dysmorphology, psychomotor retardation, progressive cerebellar ataxia, and recurrent febrile crises, usually manifesting in early infancy, accompanied by hepatosplenomegaly, lymphadenopathy, arthralgia, and skin rash. The febrile crises are similar to those observed in hyperimmunoglobulinemia D and periodic fever syndrome (HIDS). Pathogenic mutations in the mevalonate kinase gene in both disorders have demonstrated a common genetic basis. Our aim was to describe the clinical picture of adolescent patients with mevalonate kinase deficiency and to expand the clinical and biochemical spectrum of mevalonate kinase deficiency, particularly with regard to HIDS. - Methods. We report the clinical history and biochemical findings of 3 patients with mevalonic aciduria. - Results. In 2 siblings with mevalonic aciduria, a 15-year-old girl and a 14-year-old boy, the phenotype shifted with age. Ataxia has become the predominant clinical manifestation, whereas the febrile attacks occur less frequently but as yet have not disappeared. Both of them show marked elevations of immunoglobulin D (IgD). Psychomotor development is retarded but not regressive. Short stature developed in both patients. Additional findings include the development of retinal dystrophy and cataracts in both of them. The third patient is a 6-year-old boy who presented at the age of 5 years with cerebellar ataxia and retinal dystrophy. He is different from all known patients with mevalonic aciduria because of the mild neurologic involvement and because he has never developed febrile crises. In addition, levels of IgD were repeatedly normal. - Conclusion. The clinical and biochemical spectrum of patients with mevalonic aciduria is heterogeneous. Manifestations of the disease seem to be age dependent, as evident from this first report of adolescent patients. In patients who survive infancy, short stature, ataxia caused by cerebellar atrophy, and ocular involvement with retinal dystrophy become predominant findings. Recurrent febrile crises seem to diminish with increasing age and may not even be an obligatory finding. Elevation of IgD is most likely a secondary phenomenon that seems to be linked to recurrent febrile crises.